“Querendo ou não a gente se expressa”: gênero, sexualidade e LGBTfobia no cotidiano escolar de jovens LGBTQIA+ teresinenses - Ribeiro, Ariadine Cristine Gonçalves (2023)
After the family, the school is recognized as an important institution for the socialization of individuals to society. In it, the multiplicity of identities and subjectivities are gathered, however, historically they have not been willing to deal with the diversity that it gathers, but to assimilate it in the schooling process (LOURO, 1997). The present work intends to carry out an analysis on gender, sexuality and homophobia in the school environment, reflecting its relational dynamics in the construction and reproduction of prejudices that mark the journey of students who do not correspond to gender and/or sexuality norms. The school environment is investigated from the perspective of students in order to understand, based on the narratives of the experiences of LGBTQIA+ young people, how the school environment in Teresina can be hostile or welcoming to people who do not correspond to heterosexuality. It is, therefore, about thinking about the space that these young people occupy at school. It seeks to verify the construction of gender as social and cultural and the standards of normality that are understood at school, as well as the expressions of violence that occur due to intolerance. Reflecting on the reproduction of markers of difference grounded in the notion of sexed binary gender. As it has presented a research of faith carried out during the period of the Covid-19 pandemic, there was no direct contact with the students, digital mechanisms being used as tools to carry out this dialogue. An analysis was made of the data collected from the students about their experiences at school, with the aim of perceiving, from their reports, the indicators of homophobia in the school environment. It was found that young people have an understanding of gender diversity and recognize that their expressions are related to homophobia. It is observed that there is a new movement among LGBTQIA+ young people of self-affirmation at school in which they seek to claim their right to (r)exist in this space. In addition, it is noted that there has been a change in relation to the perception of homophobia, if before it was more expressed, now it is found less explicitly, so that it sometimes goes unnoticed by the students.